Students’ satisfaction on learning calculus using open and distance learning method during COVID-19 pandemic - Rusliza Ahmad; Zulkifli Mohd Ghazali; Muhammad Syawal Abd Halim (International Journal of Evaluation and Research in Education (IJERE), 2022)
In early 2020, due to the COVID-19 outbreak in Malaysia, all higher education institutions had to switch from face-to-face learning to open and distance learning (ODL) method. The main purpose was to prevent any further spread of the COVID-19 virus. This study aimed to identify factors carrying impacts on students’ satisfaction in learning calculus using ODL method. The sample consists of 224 students of Universiti Teknologi MARA (UiTM) Perak Branch, Tapah Campus who took calculus subjects using ODL method during the COVID-19 lockdown in Malaysia. Five factors are found to influence students’ satisfaction towards ODL method: student-lecturer interaction; lecturer performance; ODL course evaluation; design; and technical. By using partial least square (PLS)–SEM method, the results showed that lecturer performance has a large effect size on students’ satisfaction. Technical and design factors have medium effect sizes, while the ODL course evaluation and student-lecturer interaction have small effect sizes. This research provided useful insights for an effective planning of online calculus courses by considering all factors that influence students’ satisfaction.